1994
DOI: 10.1190/1.1443536
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of factors influencing compressional‐ and shear‐wave velocities and attenuations in tight gas sandstones

Abstract: Results are presented for compressional and shear velocities and attenuations in fully brine-saturated tight gas cores with porosities from 3 to 11.9 percent and clay contents from 1 to 38 percent. The influence of porosity, clay content, frequency, and stress on velocities and attenuations were examined using the amplitude spectra of P-and S-waves in the frequency domain. Attenuations of samples were obtained using the spectral ratio method. For a few selected samples the attenuations were also measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 14 publications
1
18
0
2
Order By: Relevance
“…Their quality factor-clay relationship has been confirmed by Tutuncu et al (1994) for tight gas sandstones measured at ultrasonic frequencies in the laboratory. Tang & Strrack (1995) have demonstrated a significant difference between the quality factors of clean and shaley sandstones from sonic log data.…”
Section: 'Terminal' Attenuation At High Pressure: Sandstones and Shalesmentioning
confidence: 60%
“…Their quality factor-clay relationship has been confirmed by Tutuncu et al (1994) for tight gas sandstones measured at ultrasonic frequencies in the laboratory. Tang & Strrack (1995) have demonstrated a significant difference between the quality factors of clean and shaley sandstones from sonic log data.…”
Section: 'Terminal' Attenuation At High Pressure: Sandstones and Shalesmentioning
confidence: 60%
“…This may be the result of a grain contact "softening" effect caused by the presence of the clays. Tutuncu et al 9 also observed this "softening" effect in experiments.…”
Section: Resultsmentioning
confidence: 78%
“…Tutuncu et al 9 describe these experiments. An acoustic gel had been applied to the ends of the cores to provide acoustic coupling with the load-frame transducers.…”
Section: Resultsmentioning
confidence: 99%
“…Usual data show decrease of wave velocity, the increase of attenuation with increasing amplitude (Mavko, 1979;Ostrovsky and Johnson, 2001;Tutuncu et al, 1994;Winkler et al, 1979). Other data show unusual increase of wave velocity and the decrease in attenuation (Johnston and Toksoz, 1980;Mashinskii, 2004;Mashinskii, 2007a;Zaitsev et al, 1999).…”
Section: Introductionmentioning
confidence: 83%